2004
DOI: 10.1021/jm0497949
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 1-(3‘-Aminobenzisoxazol-5‘-yl)-3-trifluoromethyl-N-[2-fluoro-4- [(2‘-dimethylaminomethyl)imidazol-1-yl]phenyl]-1H-pyrazole-5-carboxyamide Hydrochloride (Razaxaban), a Highly Potent, Selective, and Orally Bioavailable Factor Xa Inhibitor

Abstract: Modification of a series of pyrazole factor Xa inhibitors to incorporate an aminobenzisoxazole as the P(1) ligand resulted in compounds with improved selectivity for factor Xa relative to trypsin and plasma kallikrein. Further optimization of the P(4) moiety led to compounds with enhanced permeability and reduced protein binding. The SAR and pharmacokinetic profile of this series of compounds is described herein. These efforts culminated in 1-(3'-aminobenzisoxazol-5'-yl)-3-trifluoromethyl-N-[2-fluoro-4-[(2'-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(76 citation statements)
references
References 22 publications
4
70
0
2
Order By: Relevance
“…Based on 65, a series of aminobenzisoxazoles, represented by 71 (fXa K i 5 0.09 nM, fIIa K i 5 6,300 nM, trypsin K i 45,200 nM), was evaluated. 145,146 However, 71 showed poor permeability, poor solubility, and low oral bioavailability (2% in dog). More basic and water-soluble moieties were incorporated into the terminal group on P4 in order to improve the potency and pharmacokinetic profiles, for example, 72 (fXa K i 5 0.16 nM, fIIa K i 5 400 nM, trypsin K i 42,500 nM, F 5 38% in dogs) and 73 (fXa K i 5 0.21 nM, fIIa K i 5 300 nM, trypsin K i 41,600 nM, F 5 43% in dogs).…”
Section: Synthetic Direct Fxa Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on 65, a series of aminobenzisoxazoles, represented by 71 (fXa K i 5 0.09 nM, fIIa K i 5 6,300 nM, trypsin K i 45,200 nM), was evaluated. 145,146 However, 71 showed poor permeability, poor solubility, and low oral bioavailability (2% in dog). More basic and water-soluble moieties were incorporated into the terminal group on P4 in order to improve the potency and pharmacokinetic profiles, for example, 72 (fXa K i 5 0.16 nM, fIIa K i 5 400 nM, trypsin K i 42,500 nM, F 5 38% in dogs) and 73 (fXa K i 5 0.21 nM, fIIa K i 5 300 nM, trypsin K i 41,600 nM, F 5 43% in dogs).…”
Section: Synthetic Direct Fxa Inhibitorsmentioning
confidence: 99%
“…145 The dimethylaminomethylimidazoyl moiety of 74 further improved the selectivity against trypsin and the oral bioavailability while maintaining potency established in the aminobenzisoxazoles. The cocrystal structure of 74 bound to fXa (PDB code 1Z6E) showed that the aminobenzisoxazole binds to the S1 pocket.…”
Section: Synthetic Direct Fxa Inhibitorsmentioning
confidence: 99%
“…Modification of the DPC423 series has led to additional orally bioavailable FXa inhibitors, including razaxaban (DPC906, BMS-561389, Fig. 1) [4]. In this study we evaluated the efficacy of this potent and selective FXa inhibitor in prevention of arterial thrombosis in a rabbit model of the electrolytic injury-induced carotid artery thrombosis (ECAT) [5] and examined its ex vivo effects on coagulation parameters to confirm its selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we evaluated the efficacy of this potent and selective FXa inhibitor in prevention of arterial thrombosis in a rabbit model of the electrolytic injury-induced carotid artery thrombosis (ECAT) [5] and examined its ex vivo effects on coagulation parameters to confirm its selectivity. We selected rabbits as the animal model because razaxaban has similar potency in inhibiting human and rabbit FXa (K i = 0.19 nM in human and 0.16 nM in rabbit) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Razaxaban (37; Schema 14) war in Phase II der klinischen Entwicklung. [53] Seine Molekülstruktur wurde von dem für Trypsin nicht so selektiven FXa-Inhibitor DPC423 (36) abgeleitet. DPC423 war mit seiner gegenüber einem Benzamidin abgeschwächt basischen Benzylamin-P1-Gruppe oral bioverfügbar.…”
Section: Angewandte Chemieunclassified